The Impact of Sequencing Depth on the Number of Transcript Splice Variants Revealed by MinION Nanopore Sequencing - Ptitsyn, K.G.; Kozlova, A.S.; Khmeleva, S.A.; Kurbatov, L.K.; Radko, S.P.; Ilgisonis, E.V.; Lisitsa, A.V.; Ponomarenko, E.A. (Biomedical Chemistry: Research and Methods, 2025)
Alternative splicing (AS) of a precursor mRNA is a fundamental regulatory process implicated in physiology and pathology. The long-read RNA sequencing with a nanopore sequencer such as ONT MinION allows for direct AS profiling. In this study the impact of sequencing depth on the number of transcribed genes and the overall number of transcripts (splice variants), revealed by MinION-based sequencing, has been investigated. This is of importance in AS profiling for the issue of comparability for biospecimens analyzed in different MinION runs. The sequencing depth was described in terms of the output of high-quality mapped reads produced by a MinION sequencer. The human liver tissue samples and hepatocytederived cell lines HepG2 and Huh7 were employed as model objects. It has been found that the yield of detected genes and transcripts substantially depends on the sequencing depth. While the number of transcribed genes levelled off at about 12 thousand when the reads output exceeded 1.2 million, the number of revealed transcripts steadily increased up to about 20 thousand splice variants at the highest reads output of 2.3 million, achieved in the study. At that reads output, the ratio of the number of revealed transcripts to that of genes was slightly below 1.7. The yield of more than 2.3 million high-quality mapped reads would be required in the MinION-based nanopore sequencing to approach the level of 1.8 transcripts (splice variants) per gene, expected from the known numbers of annotated genes and transcripts for human genome. The sequencing data used were produced for human liver tissue and hepatocyte-derived cells and it is still to be seen whether the findings are general and valid for other types of cells and tissues.